Climate-change mitigation strategies at the level of a forestry company in the light of age-class legacy effects - Attila Borovics; Éva Király; Péter Kottek (Annals of Forest Science)
Abstract Key message We analyzed the future carbon balance of 47,000 ha of forests dominated primarily by Scots pine (Pinus sylvestris L.) and managed by the Szombathely Forestry Company in Hungary. Biomass, harvested wood products, and substitution effects were considered. Strong age-class legacy effects predetermine the biomass pool to turn into a carbon source with increased harvest. The highest harvesting intensity scenario proved most favorable for the overall carbon balance up to 2055. Context Forests and wood utilization play a key role in climate change mitigation by enhancing carbon sinks, increasing offsite carbon stocks, and promoting resource efficiency through material and energy substitution. Aims This case study examines the 47,000 ha forest managed by the Szombathely Forestry Company in western Hungary, dominated by climate-vulnerable coniferous species. Climate projections for the region indicate an inevitable shift to climate-resilient broadleaved species, requiring increased harvesting and regeneration. The study analyzed age-class structure, wood mobilization potential, and future carbon balances to assess the climate change mitigation impacts of intensified harvesting. Methods We used the Forest Industry Carbon Model, a yield table-based tool specifically designed to integrate data from the Hungarian Forest Authority’s database and to simulate forest stand-based carbon stock changes, wood product carbon balances, and substitution effects. We examined the future carbon balance under a business-as-usual scenario and scenarios with final harvest areas expanded by 10%, 20%, 30%, and 40%. Results Our analysis revealed strong age-class legacy effects, with a large area approaching harvesting age, signaling a key management decision. Our simulations indicated that biomass would become a carbon source if harvesting intensity increased by more than 10%, while a 40% increase was the most favorable scenario for the overall forest industry carbon balance. Conclusions We conclude that the company should base its management decisions on the broader carbon balance of the forest-based sector, while adhering to the Forest Authority’s harvesting age prescriptions to ensure long-term sustainability.